From alliance building to strategic partnerships:a historical analysis of defence diplomacy - Khalid, Faiq Hassan (2024)
Defence diplomacy within the sphere of statecraft is experiencing rapid growth due to the geopolitical and geo-economic interests of rising power blocs around the world. This paper aims to provide a comprehensive historical background of significant activities undertaken in modern defence diplomacy. The central research question explores how the activities in defence diplomacy have shaped the landscape of international relations. It is found that defence diplomacy activities like military exchanges, exercises and cooperation with roots in antiquity, have continuously adapted to shape history and remain relevant in today’s complex international relations.